Pseudoaneurysm of the descending aorta two decades after aortic coarctation repair: a case report - Ruofan Zhou; Yabo Wang; Qi An (Journal of Cardiothoracic Surgery)
Abstract Background Pseudoaneurysm after coarctation of the aorta (CoA) repair is a rare but severe complication. Contributing factors may include infection, hypertension, aortic wall weakness, and turbulent blood flow at the repair site. Case presentation A 35-year-old male presented with recurrent episodes of epistaxis and dizziness was admitted to the emergency department. He had a history of CoA repair and ventricular septal defect closure 17 years ago. Physical examination revealed elevated blood pressure. Initially, aortic dissection was suspected, but the actual diagnosis was pseudoaneurysm just distal to the left subclavian artery. Surgical intervention involved excision of the pseudoaneurysm and replacement with a new vascular graft via a dual approach of median sternotomy and left thoracotomy. Postoperative recovery was uneventful, and follow-up imaging at one month showed satisfactory aortic morphology. Conclusions This case underscores the critical role of precise imaging in differentiating pseudoaneurysms from other lesions in post-CoA repair patients. Pseudoaneurysms can present subtly yet carry substantial risks, making regular imaging follow-up essential for early detection and improved outcomes.